Employee Stock Bonus and Financial Performance: Evidence From Taiwan's Electronic Industry - Chen, Hsiang-Lan; Jiang, Ching-Hai; Huang, Yen-Sheng (Indian Journal of Finance, 2009)
This paper examines how employee stock bonus influences financial performance for electronic firms listed on the Taiwan Stock Exchange over the sample period 1996-2001. The empirical result indicates that the average return on equity is significantly higher for firms distributing employee stock bonus than those not distributing such incentive. Additionally, via Du Pont Identity, the result shows that firms distributing employee stock bonus are associated with significantly higher profit margin and asset turnover ratio, and lower financial leverage. The evidence thus is consistent with the argument that employee stock bonus can be an effective incentive mechanism to attract, retain and motivate talented personnel, and leads to enhanced financial performance as an end result.